Comparative phytochemical characterization and bioactivity evaluation of hemp (Cannabis sativa L.) root extracts using green extraction technologies - Korkmaz, Nesrin; Yaman, Cennet; Guclu, Ebru; Dogan, Uzeyir; Imamoglu, Rizvan; Korkmaz, Sengul Engul Aslan (Elsevier, 2026)
This study investigates the largely untapped therapeutic potential of industrial hemp (Cannabis sativa L.) roots, which are usually discarded as agricultural byproducts. The phytochemical composition and biological activities of extracts obtained using Soxhlet, ultrasound-assisted extraction (UAE), and supercritical COQ (SC-COQ) techniques were comparatively evaluated. Compounds were characterized using FTIR, GC-MS, LC-MS, and ICP-MS. SC-COQ extraction yielded the most chemically diverse profile, particularly enriched in fatty acids and triterpenoids. In vitro assays demonstrated that SC-COQ and Soxhlet extracts significantly promoted fibroblast migration and reduced inflammatory responses compared to UAE extracts. Gene and protein expression analyses further supported these bioactivities. In conclusion, this study highlights the phytopharmaceutical potential of hemp root extracts obtained using alternative extraction techniques, including supercritical COQ extraction. While SC-COQ extraction enabled the recovery of a chemically diverse extract, the present study focuses on comparative phytochemical and bioactivity outcomes rather than a quantitative assessment of environmental sustainability. The findings support further investigation of hemp roots, currently treated as an underutilized biomass, for potential applications in natural product research.
Keywords: Cannabis Sativa L.; Hemp Root; Green Extraction; Wound Healing; Anti-Inflammatory; Phytochemistry; Sc-Co 2; Soxhlet; Ultrasound-Assisted Extraction